ANALISIS TINGKAT KUALITAS DADIH KERBAU DENGAN PEMBERIAN JENIS PAKAN BERBEDA - Irda Sayuti '; Zulfarina ' '; Zulfaida Kurni Aurianti (Program Studi Pendidikan Biologi, 2014)
The research aims to know the influence of type of feed buffaloes to the quality ofcurd in Kampar Regency are carried out in the laboratory of Biology EducationFaculty of Teacher Training and Education and Chemical Result of Fisheries Facultyof fisheries University of Riau from July-September 2013. The research method usedis experimental descriptive. Samples of the milk comes from different types of feedthat is fodder grasses, grass-added rice straw, and grass-added rice and coconut milk.The research parameters include total bacterial colonies, protein content, fat content,and pH of curd were analyzed by descriptive. The results of research showed that thehighest total bacterial colonies 3,3 x 10 7 Cfu/ml and the highest acidity is pH 5contained in the curd with the type of fodder grass-added rice straw, the highestprotein content found in curd from type of fodder grasses 9,09%, and the highest fatcontent found in curd from type of fodder grass-added rice and coconut milk 12,95%.Keywords: Curds, Types of Feed